Tax Compliance in the School Environment: Uncovering the Role of Tax Awareness, Knowledge, and Sanctions at Petra Alpha School, West Jakarta - Hutapea, David Jeremia (Jurnal Pendidikan Makarios, 2024)
The objective of this research is to investigate the relationship between taxpayers' awareness, taxpayers' knowledge, and tax compliance. Additionally, it aims to examine the impact of tax penalties on tax compliance. This study was conducted at the Petra Alpha Education Foundation across all levels, from Kindergarten (KB) to Senior High School (SMA). Each unit has teachers and school staff with varying perspectives on taxation in Indonesia. The research methodology employed in this study is quantitative, involving in-depth analysis of factual data by using Attribution theory by Fritz Heider (1958). The techniques used for this research include descriptive statistical analysis, and the tool utilized is multiple linear regression. Based on the test results, 1) it was found that there is a significant influence of taxpayers' awareness and taxpayers' knowledge on tax compliance. 2) It is shown that higher levels of taxpayers' awareness and knowledge led to increased tax compliance, and conversely, higher tax compliance results in greater taxpayers' awareness and knowledge. 3) However, there is no significant impact of tax penalties on tax compliance. In other words, as tax penalties increase, tax compliance tends to decrease, and vice versa. The dissemination of tax penalty information to the public or taxpayers is an effective means to enhance tax compliance.